Association of time to groin puncture with patient outcome after endovascular therapy stratified by etiology - Zhang, Yiran; Hong, Lan; Ling, Yifeng; Yang, Lumeng; Li, Siyuan; Cheng, Xin; Dong, Qiang (Frontiers in Aging Neuroscience, 2022)
Background Randomized clinical trials and large stroke registries have demonstrated a time-dependent benefit of endovascular treatment (EVT) in patients with acute ischemic stroke due to large vessel occlusion. This study aimed to investigate whether this could be applied in different stroke subtypes in a real-world single-center cohort. Methods Consecutive ischemic stroke patients with large vessel occlusions presenting within 24 hours after symptom onset were prospectively registered and retrospectively assessed. Baseline multi-modal imaging was conducted before EVT. Independent predictors of functional independence (90 day modified Rankin scale 0-2) and any incidence of intracranial hemorrhage (ICH) were explored using stepwise logistic regression model in the entire cohort and in stroke subtypes. Results From 2015 to 2020, 140 eligible patients received EVT, of which 59 (42%) were classified as large artery atherosclerosis (LAA)-related. Time from last known normal to groin puncture was identified as an independent predictor for functional independence in patients of cardioembolic (CE) subtype (OR 0.90 per 10 minutes; 95% CI 0.82-0.98; P=0.013), but not in LAA subtype and the whole cohort. Groin puncture within 6 hours after time of last known normal was associated with a lower risk of any ICH in the whole cohort (OR 0.36, 95% CI 0.17-0.75, P=0.007). Sensitivity analysis of patients with complete imaging profiles also confirmed the above findings. Besides, compared with patients of CE subtype, LAA subtype had a smaller baseline ischemic core volume, a better collateral status, a slower core growth rate and numerically smaller final infarct volume. Conclusion Faster groin puncture has a more pronounced effect on the functional outcome in patients of CE subtype than those of LAA subtype. Reducing time to groin puncture is of great importance in improving the prognosis of patients after EVT, especially those of CE subtype, and reducing the incidence of any ICH in all patients.